THE INFLUENCE OF THE BANDWAGON EFFECT, DIGITAL PAYMENT, AND INCOME ON PURCHASE DECISIONS FOR THE KOREAN WAVE ASSOCIATED PRODUCT - Lumban Gaol, Rachel Millenia; Wahyudi, Setyo Tri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The number of enthusiasm about the Korean Wave is on the rise. This remains across Indonesia as well, allowing for a yearly public consumption of Korean Wave items to exceed 20 million rupiahs. This study aims to determine the influence of several factors considered to drive purchasing decisions, such as the bandwagon effect, digital payments, and income on purchasing decisions for products associated with the Korean Wave (Hallyu). This research is a descriptive quantitative research in which the data collection method was carried out by distributing questionnaires to individuals who were categorized as Generation Z. The data obtained were then processed and tested using the binary logistic regression method with the Wald test method to determine the partial effect and the statistical G test to determine the effect simultaneously. The results showed that the bandwagon effect (X1) and digital payments (X2) partially had a significant effect on purchasing decisions (Y), while income (X3) partially had no significant effect on purchasing decisions (Y). Then the bandwagon effect (X1), digital payments (X2), and income (X3) simultaneously influence purchasing decisions (Y).